HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP IBUTERHADAP PERILAKU PENCEGAHAN TUBERKULOSIS PARU ANAK DI PUSKESMAS CINERE DEPOK TAHUN 2019 - Mochammad Auzan Syapoetra (2019)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis which infects the pulmonary. Cinere Public Health Center (PHC) is the PHC with the highest number of pulmonary TB patients in Depok. From January to September 2018, 7 childrens were patient of pulmonary TB at Cinere PHC. This study was conducted to determine the correlation between mother's knowledge and attitude towards preventive behavior of children's pulmonary TB age 6-11 years at Cinere PHC Depok in February 2019. This study was an observational analytical type with cross sectional approach and consecutive sampling method. These samples include 64 mothers. Spearman Rank Correlation test showed that there were low, unidirectional, and significant correlation between mother's knowledge towards preventive behavior of children's pulmonary TB with sig. (2-tailed) 0,03 and the correlation coefficient 0,272. But there was no correlation between mother's attitude towards preventive behavior of children's pulmonary TB with sig. (2tailed) 0,456. Therefore, there were an adequate, unidirectional, and significant correlation between mother's knowledge towards preventive behavior of children's pulmonary at Cinere PHC Depok in February 2019. However, there was no correlation between mother's attitude towards preventive behavior of children's pulmonary TB at Cinere PHC Depok in February 2019.